ACTIO DE DOLO MALO I OCHRONA UMÓW PRAWNIE NIEWIĄŻĄCYCH - Lambrini, Paola (Zeszyty Prawnicze, 2017)
Actio de dolo malo and Protection of Unbinding Agreements Summary Actio de dolo was probably introduced to the praetor’s edict around 90- 80 BC at the request of C. Aquilius, famous jurist. The thesis that it was Aquilius who as praetor in 66 BC introduced it himself seems improbable on account of him being in charge of the quaestio de ambitu. Actio de dolo was a praetorian action in personam with an intentio in factum concepta, penal, infamating and arbitrary. It could be acquired only within a year. A previous causae cognitio of a praetor was necessary, because the action was a subsidiary means used only in absence of any other legal protection. The concept of dolus within this action was perceived very broadly as any improper behaviour causing damage the repair of which was impossible to be obtained by other means. Actio de dolo was probably an institution exceeding the typical contractual system in a furthest manner in order to introduce new possibilities of damage repair.